2018
DOI: 10.13005/ojc/340328
|View full text |Cite
|
Sign up to set email alerts
|

Montmorillonite KSF Clay Catalyzed Microwave Synthesis of Novel Mannich bases and their Microbial Activity

Abstract: Synthesis and characterization of N-(phenylC-NMR and Mass Spectroscopy. The final compounds were tested anti-microbial culture study. In the antibacterial and anti-fungal study the compounds 1-N-(phenyl (thiomorpholino) methyl) carbamide (TBC) shows very good activity against Pseudomonas aeruginosa, Staphylococcus aureus and Escherichia coli and N-(phenyl (thiomorpholino) methyl) acetamide (TBA) shows very good activity against Penicillium species, Candida albicans and Aspergillus niger, compare to other Manni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Catalysts tested include species which have been previously tried in the nitro-Mannich reaction such as carbonates, bicarbonate and hydroxide inorganic salts (entries 2–6) ( Wang et al, 2008 ; Zhang, Liu & Liu, 2011 ; García-Muñoz et al, 2014 ), silica (entry 7) ( Mahasneh, 2006 ), basic alumina (entry 8) ( Baricordi et al, 2004 ), and KF on alumina (entry 16) ( Ballini et al, 2014 ), as well as species which have been documented to function efficiently in similar Mannich-type reactions such as Amberlite IRA-400 Cl resin (entry 10) used to catalyse the aza-Friedel Crafts reaction ( Harichandran, Amalraj & Shanmugam, 2016 ), montmorillonite K-10 (entry 12) used to synthesise numerous Mannich bases ( Arunkumar, Subramani & Ravichandran, 2010 ), PPA-silica (entry 13) used in double Mannich condensation reactions ( Vekariya, Prajapati & Patel, 2016 ) or similar C-C bond forming reactions such as Amberlyst A-21 (entry 9) used to catalyse the nitroaldol reaction ( Ballini, Bosica & Forconi, 1996 ). Since modest results were observed with different acidic and basic strengths, a number of bifunctional catalysts were tested.…”
Section: Resultsmentioning
confidence: 99%
“…Catalysts tested include species which have been previously tried in the nitro-Mannich reaction such as carbonates, bicarbonate and hydroxide inorganic salts (entries 2–6) ( Wang et al, 2008 ; Zhang, Liu & Liu, 2011 ; García-Muñoz et al, 2014 ), silica (entry 7) ( Mahasneh, 2006 ), basic alumina (entry 8) ( Baricordi et al, 2004 ), and KF on alumina (entry 16) ( Ballini et al, 2014 ), as well as species which have been documented to function efficiently in similar Mannich-type reactions such as Amberlite IRA-400 Cl resin (entry 10) used to catalyse the aza-Friedel Crafts reaction ( Harichandran, Amalraj & Shanmugam, 2016 ), montmorillonite K-10 (entry 12) used to synthesise numerous Mannich bases ( Arunkumar, Subramani & Ravichandran, 2010 ), PPA-silica (entry 13) used in double Mannich condensation reactions ( Vekariya, Prajapati & Patel, 2016 ) or similar C-C bond forming reactions such as Amberlyst A-21 (entry 9) used to catalyse the nitroaldol reaction ( Ballini, Bosica & Forconi, 1996 ). Since modest results were observed with different acidic and basic strengths, a number of bifunctional catalysts were tested.…”
Section: Resultsmentioning
confidence: 99%
“…Scheme 4 -Aminoalkylated-2-naphthols 7-30 2-Naphthol 1 was amino alkylated in the Mannich reaction using 2-carboxaldehyde thiophene as the aldehyde reagent and 1H-benzotriazole as the amine reagent (Scheme 5). The antibacterial action of this new group of Mannich reactions [31][32][33][34][35][36][37][38] versus the original list of bacteria showed that they were all passive against gram-negative bacteria but active against gram-positive bacteria at varying stages. Candidates 34 and 38, which have hydrophobic moieties in this part of the molecule, are inert against E. fecalis, suggesting that the nature of the various amino moieties in the structure of these Mannich bases induces some selectivity.…”
Section: Figure 1: Structures Of Compounds 6a-6ementioning
confidence: 99%
“…The compound N-((thiomorpholino)phenylmethyl)carbamide (43) has excellent activity against Candida albicans, Penicillium species, and Aspergillus niger in parallel with other Mannich bases. The procedure has several advantages, including being a green chemical approach, having a simple handling method, having a short reaction time, having an easy experimental setup, and using a cheap and environmentally benign kind of catalyst [36]. Various N-Mannich reactions of heterocyclic 1,3,4-thiadiazoles 47-52 (a-c) were designed and synthesized (Scheme 6), and their antimicrobial and anti-inflammatory effects were tested in vitro.…”
Section: Figure 2: N-mannich Bases For Benzimidazolementioning
confidence: 99%
“…Catalysts tested include species which have been previously tried in the nitro-Mannich reaction such as carbonates, bicarbonate and hydroxide inorganic salts (entries 2-6) [40][41][42], silica (entry 7) [43], basic alumina (entry 8) [44], and KF on alumina (entry 16) [32], as well as species which have been documented to function efficiently in similar Mannich-type reactions such as Amberlite IRA-400 Cl resin (entry 10) used to catalyse the aza-Friedel Crafts reaction [45], montmorillonite K-10 (entry 12) used to synthesise numerous Mannich bases [46], PPA-silica (entry 13) used in double Mannich condensation reactions [47] or similar C-C bond forming reactions such as Amberlyst A-21 (entry 9) used to catalyse the nitroaldol reaction [48]. Since modest results were observed with different acidic and basic strengths, a number of bifunctional catalysts were tested.…”
Section: Catalyst Screeningmentioning
confidence: 99%